2023
DOI: 10.1038/s41467-022-35264-8
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic CD8+ T cells target citrullinated antigens in rheumatoid arthritis

Abstract: The immune mechanisms that mediate synovitis and joint destruction in rheumatoid arthritis (RA) remain poorly defined. Although increased levels of CD8+ T cells have been described in RA, their function in pathogenesis remains unclear. Here we perform single cell transcriptome and T cell receptor (TCR) sequencing of CD8+ T cells derived from anti-citrullinated protein antibodies (ACPA)+ RA blood. We identify GZMB+CD8+ subpopulations containing large clonal lineage expansions that express cytotoxic and tissue h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 61 publications
1
15
0
1
Order By: Relevance
“…Furthermore, a recent study reported the presence of clonally expanded cytotoxic CD8 + T cells in the blood and synovium of ACPA + RA patients. These cytotoxic CD8 + T cells were activated by citrullinated antigens in an HLA class I-dependent manner leading to expression of pro-in ammatory and cytolytic mediators (IFNg and/or GzmB) (39).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study reported the presence of clonally expanded cytotoxic CD8 + T cells in the blood and synovium of ACPA + RA patients. These cytotoxic CD8 + T cells were activated by citrullinated antigens in an HLA class I-dependent manner leading to expression of pro-in ammatory and cytolytic mediators (IFNg and/or GzmB) (39).…”
Section: Discussionmentioning
confidence: 99%
“…Relative to ACPA-patients, T PH cells were enriched in the synovial fluid of ACPA þ RA patients, with an upregulation in the expression of GPR56 and LAG-3. Further studies are needed, but therapies that modulate targets like GPR56 hold considerable potential, considering the distinct and robust expansion of T PH cells in the RA synovium [30 ]. The recent discovery of two CD8 þ T-cell subsets has particularly improved our understanding of the role of these cells in the pathogenesis of RA.…”
Section: T Cellsmentioning
confidence: 99%
“…In addition, a cytotoxic, clonally expanded GZMB + CD8 + subpopulation was demonstrated to be activated by citrullinated peptide antigens in CCP+ RA synovium (Table 1). These cells may represent a new autoreactive T-cell subset that directly contribute to joint destruction and further provide strong rationale for additional development of therapeutics targeting cytotoxic CD8+ T cells [33 ▪ ].…”
Section: T Cellsmentioning
confidence: 99%
“…Single-cell RNA-sequencing (scRNA-seq) of RA PB and ST identified CD8 + cytotoxic T lymphocytes (CTL) expressing granzyme B and/or K 10 that were highly activated, and produce IFN-γ and TNF in response to citrullinated self-antigens in the synovium of predominantly longstanding RA patients 11,12 . Intriguingly, inguinal lymph node biopsies from asymptomatic ACPA + or rheumatoid factor (RF) + at-risk individuals as well as patients with recent-onset RA, were enriched in CD8 + memory, CD69 + and CXCR5 + TFH relative to healthy-control biopsies 13,14 , implicating CD8 + TEM in the earliest stages of the RA immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Clonally-expanded T cells have been demonstrated in ST and PB of RA patients 12,25,26,27 , and in recent-onset RA patients, highly expanded TCR clonotypes were identified in multiple joints 25,26 . However, the degree of clonal dominance (exclusive expansion of a few clones) decreased with longer disease duration 25 suggesting that repertoire studies in early disease may yield the greatest insight to disease-relevant antigens and the role of T cells in early disease.…”
Section: Introductionmentioning
confidence: 99%